(WILL MARK BRAINLIEST) answer the question in image below please follow the directions on the paper about answer as improper fraction in simplest form, Many thanks!

WILL MARK BRAINLIEST answer the question in image below please follow the directions on the paper about answer as improper fraction in simplest form Many thanks class=

Respuesta :

Nayefx

Answer:

43/24

Step-by-step explanation:

[tex] - \dfrac{3}{8} + \dfrac{13}{6} \\ = \dfrac{13}{6} - \dfrac{3}{8} \\ = \dfrac{13 \times 4 - 3 \times 3}{24} \\ = \dfrac{52-9}{24} \\ = \boxed{\frac{43}{24} }[/tex]

Answer:

43/24

Step-by-step explanation:

Fraction addition:

  • First find the LCM of the denominators 8 and 6.
  • Using the LCM find equivalent fractions.
  • Now, the denominators are same and so add the numerators.
  • Simplify.

LCM of 6 and 8 = 24

[tex]\sf \dfrac{-3}{8}=\dfrac{-3*3}{8*3}=\dfrac{-9}{24}\\\\\\\dfrac{13}{6}=\dfrac{13*4}{6*4}=\dfrac{52}{24}\\\\\\\dfrac{-3}{8}+\dfrac{13}{6}=\dfrac{-9}{24}+\dfrac{52}{24}[/tex]

              [tex]\sf = \dfrac{-9+52}{24}\\\\= \dfrac{43}{24}\\\\[/tex]

ACCESS MORE